Journal of Physics: conference Series - Lugovskoy, Andrey; Kadyrov, Alisher; Bray, Igor; Stelbovics, Andris (IOP, 2012)
The convergent close-coupling calculations of e+-Li and e+-Na collisions are reported. The target is treated as one active electron interacting with an inert ion core. The positronium formation channels are taken into account explicitly utilizing both negative- and positive-energy Laguerre-based states. A large number of channels and high partial waves are used to ensure the convergence of the cross sections.